Impact Of Underage Marriage On Divorce Rates At The Religious Court Of Samarinda (Study Directory Of The Samarinda Religious Court Decisions) - Ade Setiawan; Sy. Nurul Syobah; Akhmad Haries (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2022)
The background of this research is the impact of underage marriage on the divorce rate at the Samarinda Religious Court. This study aims to find out how the impact of marriage for underage marriage actors in contributing to the divorce rate in Samarinda and what factors underlie the occurrence of divorce in underage married couples in Samarinda. The type of this research is a literature study with a descriptive approach with documentation study data collection techniques, namely the results of the decisions published by the Samarinda Religious Court on the Supreme Court decision directory web in 2021. The data analysis technique used is content analyst, namely by analyzing the results The results of the decisions that the authors found in the decision directory are the divorce decisions of underage marriage couples, according to the Constitution no. 1 1974 and Law no. 16 years 2019. The results of the research that the authors found were that the divorce decisions published by the Samarinda Religious Court in 2021 were 1255 decisions, 1036 divorce case decisions. 1 1974 and Law No. 16 of 2019. The highest divorce is caused by infidelity, the results of this study that the impact of the divorce rate produced by underage married couples is not too significant compared to couples who are not perpetrators of underage marriages. Due to external factors from the couples' households as well as the culture and anthropological conditions of the city of Samarinda.Samarinda which is the provincial capital provides an adequate economic platform for underage couples to find work due to the industrial and mining sectors as well as business places in Samarinda. The results of the data that the authors found in BPS Samarinda that the working age population is 15 years and over and the number of working age population 15 years and over is 91.7%